If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -3(7 + -1x) = 11 15x + (7 * -3 + -1x * -3) = 11 15x + (-21 + 3x) = 11 Reorder the terms: -21 + 15x + 3x = 11 Combine like terms: 15x + 3x = 18x -21 + 18x = 11 Solving -21 + 18x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 18x = 11 + 21 Combine like terms: -21 + 21 = 0 0 + 18x = 11 + 21 18x = 11 + 21 Combine like terms: 11 + 21 = 32 18x = 32 Divide each side by '18'. x = 1.777777778 Simplifying x = 1.777777778
| 2m+3=88 | | 16x-5.2=-18.37 | | y=-2/3x-1 | | 2x+3-5x-7=1 | | y=1/4x+1 | | -6x+3y=2 | | 8+5a=93 | | x/0.4=60 | | 12x+18y=32 | | 10+4x=3x | | 150=0 | | 4x-2=7x+4 | | y=-1/5x-4 | | -3z+8+(-2)=-12 | | 5c-6c=1 | | 2x^2+4-240=0 | | y=1/3x-4 | | 3(2x-4)+2x=-4+9x+12 | | 14/1x-6/1=-3/1+2/1x+5/1 | | 2x+4-240=0 | | 699n+55=1194 | | a+3=a+3 | | 8x-21.25=0.5x | | 5/3x^2-x+19/6 | | 0.19n+5.95=15.83 | | 4(2x+8)=-2+3(2x+6) | | 3(4x-5)+3=9 | | 3x-2(2x+3)=5x-[2x-(7-4x)] | | 3x^2+4=-6x | | x^2-12x+36=-4 | | k/3+10=-2 | | -7(a+2)-2(a+5)=7a+8a |